Natural resource reserves sustainable use and inclusive resort development - Kateryna Kosteska; Катерина Коштеска; Poyda-Nosyk Nina; Пойда-Носик Ніна; Pojda-Noszik Nina; Robert Bacho; Бачо Роберт; Bacsó Róbert; Nevlad Vira; Невлад Віра; Pavlenko Olena; Павленко Олена (EDP Sciences, 2021)
Abstract. The article is devoted to the directions natural resources reserves formation basis on inclusive development of the territory. We consider the definition of natural resources reserve use, which unlike common understanding reserve includes the related services provided to meet the requirements of inclusive growth. The expediency of natural resources reserves use forming is considered on the example of therapeutic muds of the Kuyalnyk estuary. Today, there is a lack of funds for infrastructure development needs for state and communal enterprises that carry out their activities on the natural resources using. Such situation has developed at the state importance Kuyalnyk resort in Ukraine. Having all the natural importance competitive advantages the implementation of health activities using the therapeutic mud of the Kuyalnyk estuary, economic activity in the area is declining due to lack of funds for infrastructure development. The problem solution is possible through the natural resources reserves formation for their further use on inclusive development base. The option principle can apply in reserves of use formation, which makes it possible to calculate the break-even point. It is also necessary to pay attention to the standards for calculating tax liabilities and their further redistribution to the needs of territorial development.
https://www.e3s-conferences.org/articles/e3sconf/abs/2021/31/contents/contents.html
Keywords: Natural Resource Government Institute; economic growth; environmental safety; natural resource reserves